START WITH SIMPLE STORIES: BOOSTING EIGHTH GRADERS READING COMPREHENSION AT SMPN 19 PALU - Darna M.D Olagi; Darmawan; Wahyudin; Mochtar Marhum (Universitas Muhammadiyah Makassar, 2026)
The objective of this study is to determine whether using the Start with Simple Story (SSS) Method could improve the reading comprehension of eighth-grade students at SMP Negeri 19 Palu. A pre-experimental one-group pretest–posttest design was applied to 31 purposively selected students. Data collection was conducted using pretest and posttest assessments. The pretest was administered to measure the students' initial knowledge, while the posttest was given to measure the improvement in their reading comprehension after the treatment. The average pretest score was 32.77, while the average posttest score was 64.51. Using a significance level of 0.05, the researcher observed that the calculated t-value (7.82) was higher than the t-table value (2.042). The conclusion is that the Start with Simple Story (SSS) Method significantly improves the reading comprehension of eighth-grade students at SMP Negeri 19 Palu. These findings imply that the SSS method effectively reduces students' reading anxiety by providing accessible materials. Therefore, it is recommended that EFL teachers integrate simplified storytelling to foster early comprehension success.